Teacher’s Beliefs and Practice of Learner-Generated Material in a Flipped-Speaking Class - Lailatun Nurul Aniq; Khairani Dian Annisa; Diah Kristina (Langkawi: Journal of The Association for Arabic and English, 2020)
The practice of learner-centered approach (LCA) in enhancing foreign language teaching-learning process has been broadly recognized. Little research, however, have disclosed how this approach works and promotes learners’ improved abilities. While learner-generated material (LGM) is a principle of and one of the activities in learner-centered approach, it is currently under studied, thus little researchers discuss how it applies in EFL context. This qualitative case study investigated the teacher’s belief and classroom practice of learner-generated material in a flipped speaking class. The participant of the study was a teacher in a vocational high school. The instruments were participant observation, semi-structured interview, and documentation. The analysis showed that the teacher’s belief was mostly consistent with her classroom practices, i.e. beliefs about learning objectives, teaching modeling, and procedure of learner-generated material, teaching resources, classroom management, teacher’s role, students’ role, and assessment. Nevertheless, there were little discrepancies, e.g. teachers’ beliefs about classroom procedure. The present study recommends that teachers, especially those new to LGM, follow the present findings in order to recognize the aspects within LGM in the umbrella of LCA and understand how these methods practices. The implication of the study is this research will give a contribution in Indonesian ELT context by providing a new perspective of learner-centered approach through technology.